Cláusula de não indenizar: proposta de revisão dos requisitos de validade a partir da noção de risco em contratos empresariais - Azevedo, Ciro Rangel (2024)
This thesis suggests a proposal for the revision of the validity requirements of the exclusion and limitation of indemnification clause in business contracts from the phenomenology notion of risk, deemed as a product resulting from the analysis of probability and impact arising from adverse events which may occur throughout the contractual program. The exclusion and limitation of indemnification clause has already been explored by academic works in Brazil and abroad, which refer to determined legal requirements to ascertain its validity. This work suggests to review these legal requirements, introjecting the essential notion of risk and its allocation between the parties through the exclusion and limitation of indemnification clause, as expressly permitted by the economic freedom law, in order to comprehend the real utility and function of this clause in the universe of the complex business contracts. In this context, this work will carry out an investigation with regards to (i) the risk as economic and social phenomenon, (ii) the private autonomy of the parties, as a core principle that supports the free allocation of contractual risks through the most diverse provisions, and (iii) the business contracts, which are agreements that have a singular logic based on the market and risk allocation. Risk is extracted from the analysis of the binomial probability-impact over the most varied events that may happen throughout the contractual program, including the breach and its effects, which encompass the damages. In this sense, this work seeks to explain in what manner the exclusion and limitation of indemnification clause agreed on business contracts in the full exercise of private autonomy has its basis in the logic of risk management, notably the effects of indemnification arising from a potential contractual breach, converting it into a protected legal interest. Finally, this work addresses the review of the legal requirements of the exclusion and limitation of indemnification clause, as commonly treated by the traditional doctrine, with the background of the comprehension of risk as a product of the analysis of probability and impact in the legal relations, notably in complex economic transactions governed by business contracts. This approach shall permit to comprehend the possibility of establishing the exclusion and limitation of indemnification clause in business contracts, even in hypothesis traditionally deemed as invalid by the traditional doctrine, provided that legitimate legal interest is present, including the activity related to risk management arising from the contract